2012
DOI: 10.1111/j.1460-2695.2012.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative numerical study of combined cold expansion and local torsion on fastener holes

Abstract: A B S T R A C T Cold expansion and local torsion processes provide controllable strengthening mechanisms for a fastener hole and therefore have engineering significance. They rely on the residual stress and the accumulated shearing strain, respectively, which are difficult to measure. Due to the complex closed form solutions for these mechanisms, their numerical study is of great importance. In this work, a combination of the cold expansion and the local torsion on a fastener hole has been investigated numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…For this reason, the local amplitude, depending on both the remote stress and interference level, has been calculated and analysed. Therefore, some FEA have been carried out in order to confirm what is stated earlier . In Fig.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…For this reason, the local amplitude, depending on both the remote stress and interference level, has been calculated and analysed. Therefore, some FEA have been carried out in order to confirm what is stated earlier . In Fig.…”
Section: Resultsmentioning
confidence: 62%
“…The holes cause a geometrical discontinuity, which leads to stress concentration during the loading; furthermore, the drilling operation creates rough surfaces or localised damages, so that the fatigue life of component may be drastically reduced. Such situation forces a compensation of the fatigue life reduction that can be obtained with different techniques such as the cold expansion or the interference‐fit connections . The aim of the present paper was to characterise, from a microstructural and mechanical point of view, the 35 KB2 forging steel, investigating the effect of interference‐fit level on the fatigue life of holed plates, which are used in tracks chains of high power excavators (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no known reports of FSP performed on cylindrical or curved surfaces. Recently, Shamdani and Khoddam [22] performed a numerical study on a combination of cold expansion and local torsion on fastener holes. Although the results were not experimentally verified, they concluded that cold expansion combined with local torsion would have a beneficial effect on improving the overall mechanical performance of a hole.…”
Section: Introductionmentioning
confidence: 99%
“…An idea for a modified torsion straining, called internal torsion, was demonstrated, as an alternative to the existing mandrel cold working methods. The same authors offer a combination of mandrel cold working and local torsion of fastener hole, considering an idealized case . The material used is a Ti‐IF steel.…”
Section: Introductionmentioning
confidence: 99%